Pengaruh Motivasi Belajar dan Lingkungan Sekolah terhadap Hasil Belajar Akuntansi Siswa Kelas X SMK Negeri 1 Solok Selatan - Melda Elya, Yetri; Tanjung, M.S, Dra. Mirna; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACT The purpose of this study is to obtain empirical evidence about the influence of family background and motivation of students to learn the financial results of class X students of SMK Negeri 1 Sur Solok. The method used in this study is descriptive and causal. This research is a saturated sample or census, where the sampled population is used by 60 students from a population of 60 students. Learning Motivation data (X1) and the school environment (X2) is obtained from the results of the questionnaire or questionnaire, while representing student learning outcome data (Y) is obtained from the documentation of the final value 1st half of 2013/2014 school year. The analysis of the data used in this study is a descriptive analysis and inductive analysis consisting of the classical assumption test, multiple regression analysis and hypothesis testing. The results of this study indicate that: 1. Motivation significant and positive impact on the learning outcomes of accounting students of class X of SMK Negeri 1 Sur Solok, 2. School Climate significant and positive impact on the learning outcomes of accounting students of class X of SMK Negeri 1 South Solok, 3. The motivation to learn and the school environment jointly significant effect on learning outcomes of accounting students of class X of SMK Negeri 1 Sur Solok. Based on these results, it is suggested that students, teachers and school authorities to pay more attention to another student motivation to learn how teachers motivate their students to increase learning outcomes of students and school facilities and environment separti infrastructure, the environment around the school in an effort to optimize the results further learning accounting class X SMK Negeri 1 South Solok.